Formulasi dan Uji Stabilitas Fisik Sediaan Gel Ekstrak Daun Ketepeng Cina (Cassia alata L.) - Sayuti, Nutrisia Aquariushinta (Jurnal Kefarmasian Indonesia, 2015)
Cassia alata L. leaf contains flavonoids which have anti-inflammatory, anti-allergy, antioxidants and antifungal effects. The traditional application of it requires long preparation time so we need a formulation with more practical and durable storage is needed. Gel formulation was chosen because it is easy to dry, forming an easy to wash film layer and give a sense of cold on the skin. Gel components affect the stability of the gel. Physical stability is analyzed to ensure that the formulated gel’s quality, safety and benefits meet the specifications and survive during storage. This study aimed to create a gel formula and analysed its physical stability test of Cassia alata L. leaf extract gel. Research design adopted in this study was an experimental laboratory. Optimum gel formula determined by variations in the concentration of sodium carboxymethyl celulose (CMCNa). Gel that meet the criteria of homogeneity, consistency, pH and spreadibility was set as the optimum formula. Physical stability of optimum formula was analyzed by organoleptic, homogeneity test, pH test, viscosity test and spredability test. Gel that meets the acceptance criteria are Cassia alata L. leaf extract gel with CMC-Na concentration of 3% those determined as the optimum formula. Stability analysis of optimum formula didn’t show any changes in pH, color, smell and taste, although it changes of the shape, viscosity and spreadibility were found. The optimum formula gel obtained by the concentration of CMC-Na 3%. results were less stable during the 8 weeks of storage at a temperature of 40°C.